POLITIK PEMBANGUNAN DALAM LOGIKA DEMOKRASI REPRESENTATIF : (Studi Kasus Pembangunan di Kabupaten Lamongan) - Ahmad Burhan Hakim; Satryo Pringgo Sejati (The Republic : Journal of Constitutional Law, 2024)
Democracy is a political system that is widely used by many countries in the world, including Indonesia. Elections are something that is closely related to democracy. So it has a series of presidential elections, regional head elections and legislative elections. In its development, regional elections have become a magnet that attracts many parties to conduct research. On the basis that there will be good development in a democratic manner with regional elections as an integral part of the regional autonomy system. Thus, there is great hope that the results of the regional elections will create equitable development with the assumption that regional money management will be maximized. It's just that that's not what happened, so we tried to carry out a simple study about development based on representation of support, not because of the needs of the area. This then happened in Lamongan, where there was a development gap, the Pantura area saw more massive development than the development in the South Lamongan area.